Empires of the Atlantic world : Britain and Spain in America, 1492-1830 - Elliott, J. H. (John Huxtable) (Yale University Press, 2006)
"Elliott identifies and explains both the similarities and differences in the two empires' processes of colonisation, the character of their colonial societies, their distinctive styles of imperial government, and the independence movements mounted against them. Based on wide reading in the history of the two great Atlantic civilizations, the book sets the Spanish and British colonial empires in the context of their own times and offers us insights into aspects of this dual history that still influence the Americas."--Jacket